Psychology - Bernstein, Douglas A.; Clarke-Stewart, Alison; . (Boston : Houghton Mifflin, 2000)
Introducing psychology. Research in psychology. Biological aspects of psychology. Sensation. Perception. Learning. Memory. Cognition and language. Consciousness. Mental abilities. Motivation and Emotion. Human development. Health, stress and coping. Personality. Psychological disorders. Treatment of psychological disorders. Social cognition. Social influence.
Keywords: Psychology; Psychology